Synergistic Use of Fly Ash and Silica Fume to Produce High-Strength Self-Compacting Cementitious Composites - Muhammad Tausif Arshad; Saeed Ahmad; Anwar Khitab; Asad Hanif (Crystals, 2021)
High-performance cementitious composites with self-compacting characteristics are gaining due importance in meeting the challenges of the modern world. This experimental study deals with developing high-strength self-compacting cement mortar composites containing a binary blend of silica fume and fly ash. Seven specimens series were prepared with fly ash (FA), ranging from 17.5% to 25%, and silica fume (SF), from 1.25% to 7.5% of the cement mass. The control specimen powder content consists of 80% ordinary portland cement (OPC), 20% FA, and 0% SF; in the remaining six series of specimens, OPC is kept constant, whereas FA is reduced by 1% and SF is increased by 1% subsequently. Rheological behavior, mechanical properties, and microstructural characteristics of the developed high-performance composites were evaluated. The optimum binary blend for achieving the maximum flow spread and flow rate of the cement mortar is reported as 80% FA and 20% SF. For superior mechanical characteristics, optimum powder content was found as 80% OPC, 17.5% FA, and 2.5% SF. Using the proposed binary blend for construction applications will produce high-strength composites and promote sustainable development due to the use of industrial wastes as OPC replacement.